Synthesis and characterisation of β-tricalcium phosphate coating on zirconia toughened alumina by biomimetic method. (April 2013) - Esfahani, H; Nemati, A; Salahi, E
Abstract : Abstract: The present work studied bioactive coatings on the surface of ceramic biomaterials. Zirconia toughened alumina (ZTA) composites containing 15 mol.-%. Partially stabilised zirconia was prepared after 1 h sintering at 1550°C. Apatite layers were then coated onto the surfaces of composites by the biomimetic method using 1·5–2 multiply concentrations of simulated body fluid (SBF). Before treatment in SBFs, a sodium silicate layer was employed as nucleating agent to induce the formation of a calcium phosphate layer. The effect of immersion time on the morphology of the precipitate was monitored with a scanning electron microscope. X dot maps revealed that there is a relationship between distribution of Ca–P and ZTA surface. X-ray diffractometry patterns, calcium/phosphor molar ratio and Fourier transform infrared spectroscopy showed that β -tricalcium phosphate and calcium deficient hydroxyapatite precipitated onto substrates via biomimetic. The thin film X-ray diffraction pattern showed that the calcium deficient hydroxyapatite decomposed into β -tricalcium phosphate and CaO after 0·5 h of heat treatment at 700°C.